GAMBARAN HASIL URINALISIS PEMERIKSAAN KESEHATAN PADA KRU KABIN DI BALAI KESEHATAN PENERBANGAN PERIODE JANUARI-MARET 2020 - Nelly Aprilyani (2020)
During the flight, pilots and cabin crew are at risk for dehydration, this is because the loss of body fluids is very sensitive to environmental changes, such as high air temperature, low air humidity, and altitude. Air humidity in the aircraft cabin is at a low level of 5-10%, this is a factor in cabin crew being prone to dehydration. The Federal Aviation Association (FAA) in 2010 recommended consuming 1.9 liters of water in 24 hours or the equivalent of 8 glasses per day. Dehydration is closely related to urinalysis, therefore, this study aims to determine the macroscopic, microscopic, and chemical description of urinalysis in cabin crew at the aviation health center for the period January - March 2020. This study is a descriptive study using a cross-sectional approach. In this study, the results of the urinalysis examination were macroscopic, the color of the urine was mostly yellow (99.32%), and the level of clear clarity (92.5%). Microscopically, all respondents found that there were bacteria (100%), most of them contained crystals (67.8%) and a few others had erythrocytes (15.0%). Chemically, the urine pH ranges from 6 (44.5%), protein (12.3%), bilirubin (2.05%), and urobilinogen (4.19%). In this study, the concern is the presence of bacteria, crystals, proteinuria, and erythrocytes in the urine. Factors that can affect the results of the urinalysis include the consumption of drugs, food, systemic diseases, and diseases of the urinary tract. Also, some respondents can be dehydrated